The Influence of Early Motor Skill Development on Technical Proficiency in Adolescent Football Players - Subhan, Ahmad; Agus Widodo Suripto (HM Publisher, 2024)
The acquisition of fundamental motor skills (FMS) during early childhood lays the groundwork for more complex motor skills and sports-specific techniques later in life. This study investigates the relationship between early motor skill development and technical proficiency in adolescent football players. A longitudinal study was conducted, tracking the motor skill development of 50 participants from ages 5 to 15. Early motor skills were assessed using standardized tests, while technical proficiency in football was evaluated through a combination of skill-specific drills and match performance analysis during adolescence. The findings revealed a significant positive correlation between early motor skill competence and subsequent technical proficiency in football. Participants who demonstrated higher levels of FMS competence in early childhood exhibited superior ball control, passing accuracy, shooting power, and overall technical performance as adolescent football players. In conclusion, the study underscores the critical role of early motor skill development in shaping technical proficiency in adolescent football players. Promoting and facilitating early FMS acquisition can significantly enhance the technical abilities of young athletes, potentially leading to improved performance and long-term success in football.